Remote workers’ wellbeing in the age of COVID-19 - Caldeira, Clara; Machado, Letícia S.; Perin, Marcelo G.; Souza, Cleidson R. B. de (2020)
ABSTRACT Social isolation measures used worldwide to reduce the impacts of COVID-19 led many office workers to work remotely with little notice. While researchers have studied remote collaboration for more than two decades, the scale and context of remote work during a pandemic is unprecedented and has changed personal and work dynamics. In this paper, we discuss the results of a survey study investigating the impact of remote work during the COVID-19 pandemic in Brazil, informed by Olson & Olson’s framework for distributed collaboration. We report preliminary findings from this study, focusing specifically on workers’ wellbeing. Our results suggest that the main factors influencing workers’ well beings are Common Ground Challenges, Collaboration Readiness, Collaboration Technology Readiness, Organizational Management, and Interruptions. Keywords distributed collaboration, wellbeing, social isolation ABOUT THE AUTHOR/S CLARA CALDEIRA University of Pará, Brazil claramcaldeira@gmail.com Clara Caldeira is a Postdoctoral researcher at University of Pará, in Brazil. She holds a PhD and Master’s degree in Informatics from UC Irvine and a Bachelor's degree in Computer Science from the University of Brasilia. She conducts research on the fields of HCI and social computing, and health informatics. LETÍCIA S. MACHADO University of Pará, Brazil leticia.smachado@gmail.com MARCELO G. PERIN Fundação Getulio Vargas, Brazil mperin25@gmail.com CLEIDSON R. B. DE SOUZA University of Pará, Brazil cleidson.desouza@acm.org New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).